Method for regulating thermal expansion coefficient of Mn3Ge material
The Mn3Ge polycrystalline material is subjected to single-axis bound thermal deformation treatment through high-pressure bound thermal deformation process, which solves the problem of continuous regulation of negative thermal expansion behavior of single-phase materials in the prior art, and effectively regulates the thermal expansion coefficient and optimizes the performance of Mn3Ge materials.
Patent Information
- Application Number
- CN202411904783.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to achieve continuous regulation of negative thermal expansion behavior in the same single-phase material, resulting in the problems of material heterogeneity, process complexity and interruption of regulation.
The high-pressure bound deformation process is used to perform uniaxially bound thermal deformation treatment on Mn3Ge polycrystalline materials. By applying large uniaxial stress and controlling temperature, Mn3Ge can be transformed from a hexagonal opposite ferromagnetic structure to a tetragonal ferromagnetic structure, and then its thermal expansion coefficient is regulated.
The thermal expansion coefficient of Mn3Ge material is adjusted from negative to zero or positive, the thermal expansion performance of magnetic negative thermal expansion materials is optimized, and its application range is expanded.
Smart Images

Figure CN119900091A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic materials, and in particular to a method for regulating the thermal expansion coefficient of a Mn3Ge material. Background Art
[0002] Most materials expand when heated due to the anharmonic vibrations of the crystal lattice. This positive thermal expansion (PTE) phenomenon is ubiquitous in everyday life. Negative thermal expansion (NTE) materials are the opposite and shrink in volume when heated.
[0003] Mn3Ge is an antiferromagnetic NTE material. The hexagonal phase of Mn3Ge is a high-temperature phase; the tetragonal phase of Mn3Ge is a low-temperature phase and is a P-type ferrimagnet, a PTE material. The hexagonal phase and tetragonal phase of Mn3Ge can be transformed by introducing thermodynamic parameters (such as pressure, temperature, etc.). For magnetic NTE materials, thermal expansion is mainly affected by the rate of magnetic phase change, so the thermal expansion behavior of Mn3Ge is directly related to the Mn magnetic moment located in the ab plane.
[0004] The synthesis methods of adjustable NTE materials mainly include material compounding and element doping. A variety of multiphase NTE materials with different temperature ranges and different thermal expansion properties have been successfully prepared to achieve the regulation of negative thermal expansion. However, these methods inevitably bring about the problems of material multiphase, process complexity and discontinuous regulation during regulation. It is still worth further exploring the continuous regulation of NTE behavior in the same single-phase material. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a method for regulating the thermal expansion coefficient of Mn3Ge material. The present invention uses a high-pressure constrained deformation process to adjust the thermal expansion coefficient of Mn3Ge polycrystalline material with negative thermal expansion behavior from negative to zero or positive, optimizes the thermal expansion coefficient of magnetic negative thermal expansion materials, and expands its application range.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention provides a method for regulating the thermal expansion coefficient of a Mn3Ge material, comprising the following steps:
[0008] The Mn3Ge polycrystalline material is subjected to uniaxial constrained thermal deformation treatment; the pressure of the uniaxial constrained thermal deformation treatment is 0.5-1.2GPa and the temperature is 385-405K.
[0009] As a preferred implementation, the thermal expansion coefficient of the Mn3Ge material is positively correlated with pressure.
[0010] In the technical solution of the present invention, the thermal expansion coefficient of the Mn3Ge polycrystalline material is a negative value; in the above method, the thermal expansion coefficient of the Mn3Ge material treated at a pressure of 0.5 to 1.0 GPa is a negative value or zero, and the thermal expansion coefficient gradually tends to zero as the pressure increases; when the pressure is 1 to 1.2 GPa, the thermal expansion coefficient of the Mn3Ge material treated by the above method reverses to a positive value.
[0011] As a preferred embodiment, the Mn3Ge polycrystalline material is prepared by high vacuum arc melting and annealing;
[0012] In certain specific embodiments, the Mn3Ge polycrystalline material prepared by high vacuum arc melting and annealing also includes a treatment process of restoring the metallic luster by polishing the surface to facilitate subsequent deformation processing.
[0013] As a preferred embodiment, the uniaxial restraint thermal deformation treatment time is 5 to 20 seconds;
[0014] Preferably, the pressure increase rate of the uniaxial restrained thermal deformation treatment is 0.05 to 0.06 GPa / s.
[0015] As a preferred embodiment, the deformation amount of the uniaxial restrained thermal deformation treatment is 8% to 65%; in the technical solution of the present invention, the deformation amount is the ratio of the downward pressure of the sample after deformation to the initial height of the sample.
[0016] As a preferred embodiment, the uniaxial restraint thermal deformation further includes a pre-deformation process, and the pre-deformation process is a uniaxial restraint deformation process; the time of the uniaxial restraint deformation process is 20 to 25 seconds;
[0017] Preferably, the pressure increase rate of the uniaxial restrained deformation treatment is 0.01 to 0.008 GPa / s;
[0018] In some specific embodiments, the Mn3Ge polycrystalline material is a cylinder; the uniaxial constrained thermal deformation treatment and the uniaxial constrained deformation treatment are carried out using a stainless steel hollow cylindrical mold; the cavity of the stainless steel hollow cylindrical mold is used to accommodate the Mn3Ge polycrystalline material; the ratio of the diameter of the Mn3Ge polycrystalline material to the inner diameter of the stainless steel hollow cylindrical mold is 6.94~7.94:7~8; the ratio of the height of the Mn3Ge polycrystalline material to the height of the stainless steel hollow cylindrical mold is 2~6:8; after the Mn3Ge polycrystalline material is loaded in the stainless steel hollow cylindrical mold, the upper and lower ends are sealed with round steel sheets.
[0019] The present invention has the following advantages and beneficial effects:
[0020] The present invention starts from changing the magnetic structure of Mn3Ge, and causes a structural phase transition from a hexagonal opposite ferromagnetic structure to a tetragonal ferrimagnetic structure in Mn3Ge by uniaxial constrained deformation, thereby realizing continuous regulation of the NTE behavior of single-phase Mn3Ge. The method provided by the present invention introduces a thermodynamic parameter, namely pressure, and applies a large uniaxial stress to the Mn3Ge polycrystal during uniaxial constrained deformation to realize effective plastic deformation of the Mn3Ge polycrystal. This method can ensure that the Mn3Ge polycrystal does not break, and a structural phase transition from a hexagonal opposite ferromagnetic structure to a tetragonal ferrimagnetic structure occurs, thereby causing a continuous transition of thermal expansion behavior from NTE to PTE. In addition, the present invention introduces a thermodynamic parameter, namely temperature, during uniaxial constrained deformation, so that the deformation environment is carried out at the magnetic transition temperature of Mn3Ge, breaks through the energy barrier of the antiferromagnetic ordered structure, and causes Mn3Ge to undergo thermal demagnetization, thereby realizing a more effective structural phase transition.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] The present invention combines uniaxial constrained deformation with thermal demagnetization technology, adopts secondary deformation in the deformation process, reasonably controls the deformation rate and temperature, and purposefully introduces lattice distortion, so as to realize a structural phase transition from hexagonal phase to tetragonal phase in Mn3Ge polycrystal.
[0023] This method is different from the existing methods of changing thermal expansion behavior through chemical pressure such as material compounding and element doping. It combines high-pressure constrained deformation with thermal demagnetization technology, and adopts secondary deformation in the deformation process to reasonably control the deformation rate. It can achieve controllable effective plastic deformation in Mn3Ge polycrystal. The purposeful introduction of effective plastic deformation can introduce a structural phase transition of Mn3Ge from hexagonal phase to tetragonal phase, thereby realizing continuous regulation of Mn3Ge's negative thermal expansion behavior to positive thermal expansion.
[0024] The method provided by the present invention is simple to operate, easy to implement, and the materials are easy to obtain. It solves the problems of material multiphase, process complexity and discontinuous regulation in the regulation of thermal expansion materials, and provides different ideas and methods for realizing negative thermal expansion behavior in different temperature ranges in single-phase or multi-phase materials, and also lays a certain foundation for the development and utilization of Mn3Ge. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a flow chart for preparing the Mn3Ge polycrystalline material sample in Example 1 of the present invention.
[0026] Figure 2 This is a sample loading flow chart of the Mn3Ge polycrystalline material sample in Example 1 of the present invention.
[0027] Figure 3These are the specific process parameters of the thermal deformation treatment in Example 1 of the present invention.
[0028] Figure 4 1 is the XRD spectrum of Mn3Ge before and after deformation and Mn3Ge tetragonal phase powder in Example 1 of the present invention.
[0029] Figure 5 1 is the thermal expansion curve of Mn3Ge before and after deformation and the Mn3Ge tetragonal phase in Example 1 of the present invention.
[0030] Figure 6 It is the MH curve of Mn3Ge before and after deformation and the Mn3Ge tetragonal phase in Example 1 of the present invention.
[0031] Figure 7 It is the MT curve of Mn3Ge before and after deformation and the Mn3Ge tetragonal phase in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0033] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0034] Example 1
[0035] Step 1: Prepare the Mn3Ge polycrystalline material sample by high vacuum arc melting method. In high purity argon gas, argon arc is generated at high temperature by ionizing argon, and Ti balls are melted before and after melting the alloy to absorb the remaining oxygen in the cavity, further reducing the oxidation of the alloy. The metal raw materials required for melting by high vacuum arc melting method are high purity Mn block (99.7%) and Ge block (99.99%), which are mixed according to the atomic ratio of Mn:Ge=3.3:1. During the melting process, in order to ensure the uniform composition of the molten alloy and avoid component segregation, the alloy is turned over and melted after cooling, and repeated 4 times. The weight loss after the complete process is less than 1%. The obtained alloy ingot is sealed in a vacuum quartz tube and annealed at 1073K for 4 days. In order to obtain a high degree of atomic order, the sample is annealed at 923K for 4 days and finally quenched in an ice-water mixture.
[0036] Step 2: If Figure 1As shown, the prepared sample 1 is in the shape of a round cake, with a diameter of about 18 mm and a center thickness of about 8 mm; there is a small amount of black Mn oxide layer on the surface, and the cross section has a bright white metallic luster; it is cut into a cylinder 2 with a diameter of D = 7.44 mm and a height of h = 4 mm by a wire cutting machine, and then the surface is polished with 1200 mesh sandpaper to restore the bright white metallic luster, and then the polished Mn3Ge polycrystal is placed in alcohol, and the impurities still attached to the surface of Mn3Ge are removed by high frequency of ultrasound, and after ultrasonic cleaning, it is blown dry for standby use;
[0037] Step 3: Use a wire cutting machine to cut a number of steel sheets 3 with a thickness of 1 mm, grind the cut discs with 1200-mesh sandpaper to remove impurities on the surface, and then use ultrasonic waves to further remove surface impurities;
[0038] Step 4: Take a stainless steel sleeve 4 with a height of h = 8mm, an outer diameter of D = 10mm, and an inner diameter of 7.5mm, and weld a pair of K-type galvanic wires 5 for temperature measurement at the center of the steel sleeve. The galvanic wires are sheathed with a hollow ceramic tube with an outer diameter of 1mm to prevent temperature from running away;
[0039] Step 5: embed the cylindrical Mn3Ge polycrystalline material sample prepared in step 2 into the stainless steel sleeve 4 of step 4, and fill and seal it with stainless steel discs 3 (step 3) of the same thickness on the top and bottom, so that the sample is fixed in the middle of the steel sleeve;
[0040] Step 6: Place the steel sleeve with the sample in step 5 into the spark plasma sintering equipment, connect the galvanic wire, and apply a pre-pressure of 0.05 GPa before deformation to avoid discharge caused by poor contact during heating; evacuate the chamber to a vacuum degree of 5×10 -4 After that, the pressure was increased to 0.2GPa at a constant speed of 20s and stabilized for 15s; the pressure was increased to 0.6GPa, 0.8GPa, 1.0GPa, and 1.2GPa at a constant speed of 0.05GPa / s, and the temperature was raised to 395K at the same time; after reaching the preset pressure and temperature, it was stabilized for 15s, and finally the pressure was slowly removed at a rate of 0.1GPa / s to complete the deformation; argon gas was filled in the chamber, and the sample was taken out after waiting for it to cool naturally to room temperature. After deformation, the sample became a round cake; the deformed sample was taken out and cut to a depth of 1mm on the outer steel sleeve by wire cutting to release the internal stress. After the release was completed, the sample was taken out, the surface was polished, and the surface impurities were further removed by ultrasound; the specific process of pressure increase and temperature increase in this step is shown in Figure 3 .
[0041] In this embodiment, the deformation amounts of the above-mentioned deformed Mn3Ge materials are 8.2%, 16.6%, 24.6%, and 37.2% respectively (arranged in order from small to large according to the deformation pressure).
[0042] Figure 4The crystal structure of the sample after deformation in this embodiment is characterized by an X-ray diffractometer. It can be seen from the figure that the (020) diffraction peak shifts to the right after deformation, the lattice parameter a decreases after deformation, the half-height width becomes wider, and the characteristic peak of the Mn3Ge tetragonal phase appears, indicating that the Mn3Ge hexagonal phase (DO) is successfully introduced during the deformation process. 22 ) to Mn3Ge tetragonal phase (DO 19 ) structural phase transition.
[0043] Figure 5 It is the thermal expansion curve of the sample and the Mn3Ge tetragonal phase before and after deformation in this embodiment. It can be seen from the figure that the thermal expansion curve of the deformed sample is between the hexagonal phase and the tetragonal phase. Therefore, compared with the Mn3Ge hexagonal phase before deformation, the constrained deformation treatment induces the Mn3Ge tetragonal phase, which changes the thermal expansion behavior of Mn3Ge and realizes the transition from NTE to PTE.
[0044] Figure 6 It is the MH curve of the sample before and after deformation and the Mn3Ge tetragonal phase in this embodiment. It can be seen from the figure that the magnetization intensity of the deformed sample is between the hexagonal phase and the tetragonal phase, indicating that the transformation from the hexagonal inverse ferromagnetism of Mn3Ge to the ferrimagnetism of the tetragonal phase of Mn3Ge is achieved during the deformation process, which is a strong proof of "deformation-induced tetragonal phase".
[0045] Figure 7 It is the MT curve of the sample before and after deformation and the Mn3Ge tetragonal phase in this embodiment. It can be seen from the figure that in the temperature range where the sample undergoes negative thermal expansion, as the temperature rises, the rate of magnetic order transformation of the deformed sample decreases with the increase of deformation pressure, and gradually approaches the tetragonal phase, indicating that deformation does induce the Mn3Ge tetragonal phase. The change in the magnetic order transformation rate is also the fundamental reason for the change in the thermal expansion behavior of Mn3Ge.
[0046] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for regulating the thermal expansion coefficient of Mn3Ge material, characterized in that: The following steps are involved: The Mn3Ge polycrystalline material is subjected to uniaxial constrained thermal deformation treatment; the pressure of the uniaxial constrained thermal deformation treatment is 0.5-1.2GPa and the temperature is 385-405K.
2. The method according to claim 1, characterized in that The thermal expansion coefficient of the Mn3Ge material is positively correlated with pressure.
3. The method according to claim 1, characterized in that The Mn3Ge polycrystalline material is prepared by high vacuum arc melting and annealing.
4. The method according to claim 3, characterized in that After the annealing, a treatment process of restoring the metallic luster by polishing the surface is also included.
5. The method according to claim 1, characterized in that The time of the uniaxial restraint thermal deformation treatment is 5 to 20 seconds.
6. The method according to claim 1, characterized in that The pressure increase rate of the uniaxial restrained thermal deformation treatment is 0.05 to 0.06 GPa / s.
7. The method according to claim 1, characterized in that The deformation amount of the uniaxial restrained thermal deformation treatment is 8% to 65%; the deformation amount is the ratio of the downward pressure of the sample after deformation to the initial height of the sample.
8. The method according to claim 1, characterized in that The uniaxial restrained thermal deformation also includes a pre-deformation process, and the pre-deformation process is a uniaxial restrained deformation process.
9. The method according to claim 8, characterized in that The time of the uniaxial restraint deformation treatment is 20 to 25 seconds.
10. The method according to claim 8, characterized in that The pressure increase rate of the uniaxial restrained deformation treatment is 0.01 to 0.008 GPa / s.